2003
DOI: 10.1207/s15516709cog2704_1
|View full text |Cite
|
Sign up to set email alerts
|

A real‐world rational agent: unifying old and new AI

Abstract: Explanations of cognitive processes provided by traditional artificial intelligence were based on the notion of the knowledge level. This perspective has been challenged by new AI that proposes an approach based on embodied systems that interact with the real‐world. We demonstrate that these two views can be unified. Our argument is based on the assumption that knowledge level explanations can be defined in the context of Bayesian theory while the goals of new AI are captured by using a well established robot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 50 publications
1
45
0
1
Order By: Relevance
“…Drawing inspiration from perceptual mechanisms of biological systems, machine perception researchers are starting to develop new perception schemes for roving robots. For example, Verschure and co-workers developed a perceptual scheme (Distributed Adaptive Control, DAC5) as a neural model for classical and operant conditioning Verschure and Althaus 2003). In DAC5 three tightly connected control layers are introduced: the reactive layer, the adaptive layer and the contextual layer.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing inspiration from perceptual mechanisms of biological systems, machine perception researchers are starting to develop new perception schemes for roving robots. For example, Verschure and co-workers developed a perceptual scheme (Distributed Adaptive Control, DAC5) as a neural model for classical and operant conditioning Verschure and Althaus 2003). In DAC5 three tightly connected control layers are introduced: the reactive layer, the adaptive layer and the contextual layer.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically we are confronted with the question of how animals arrive at useful, reproducible and, hence, stable behavioural patterns, while they are at the same time able to learn something new. Recently Verschure suggested that such systems should contain several layers for control and learning: at the bottom a reactive layer performs pure reflex-based control, an adaptive layer above performs predictive learning much in the sense of classical or operant conditioning, and finally a top contextual layer carries out higher-level adaptation (the DAC architecture, Verschure and Althaus 2003). In our study we are concerned with the first two layers only.…”
Section: Closed-loop Context: Combining Control and Learningmentioning
confidence: 99%
“…It is also important that the system have an explanation facility that can show the end user how it arrived at an answer. This explanation facility can be at the knowledge level as described by Verschure and Althaus (2003) and is typical of what is used in traditional AI applications. The knowledge level describes knowledge, goals and actions according to the principle of rationality.…”
Section: Providing Ownership In the Development Processmentioning
confidence: 99%
“…The knowledge level describes knowledge, goals and actions according to the principle of rationality. Verschure and Althaus (2003) suggest that there are several problems with this, most of which can be brought back to the dependence of solutions on the a priori specification of rules and representations. This does not appear to pose a problem in this case, because traditional approaches to development relating to problem solving and planning as described by Newell (1990), cited in Verschure and Althaus (2003) as opposed to the new AI described by the same authors as 'aimed to solve problems in the real world, incorporating most biologically motivated principles in its solutions' are used in this domain of KBDSS development.…”
Section: Providing Ownership In the Development Processmentioning
confidence: 99%